How far do shocks move across borders? Examining volatility transmission in major agricultural futures markets - Hernandez, Manuel A.; Ibarra, Raul; Trupkin, Danilo R. (International Food Policy Research Institute, 2011)
This paper examines the level of interdependence and volatility transmission across major exchanges of maize, wheat, and soybeans in the United States, Europe, and Asia. We follow a multivariate GARCH approach to explore in detail and under different specifications the dynamics and cross-dynamics of volatility in agricultural futures markets. We account for the potential bias that may arise when considering exchanges with different closing times. The period of analysis is 2004-2009 for maize and soybeans and 2005-2009 for wheat. The results indicate that there is a strong correlation among international markets. In particular, we find both own- and cross-volatility spillovers and dependence between most of the exchanges. There is also higher interaction between the United States (Chicago) and both Europe and Asia than within the latter. The results further show the major role Chicago plays in terms of spillover effects over the other markets, particularly for maize and wheat. For soybeans, both China and Japan also exhibit important cross-volatility spillovers. Finally, the level of interdependence between exchanges has not necessarily increased in recent years for all commodities. From a policy perspective, these findings suggest that any potential regulatory scheme to address (excessive) price volatility in agricultural exchanges should be coordinated across markets; localized regulation will have limited effects given the high level of interrelation between markets.